Mouthguard for Orthodontic Patient Trumpet Player - Maria João Ponces (2013)
Mouthguards reduce the occurrence and the severity of damages on intraoral tissues absorbing and diffusing the energy of the impact. The brass instruments, also known as 'lip-vibrated instruments, are played by propelling air through sealed lips. The pressure applied on the lips can cause damage and bruising. The use of mouthguards can prevent those injuries producing some relief on orthodontics patients playing those instruments. The aim of this work was to describe the procedures to construct a custom mouthguard for orthodontic patient trumpet player (MOPTP) that prevents injuries on soft tissues while it allows simultaneously orthodontic tooth movement and a good musical performance.